Mississippian Village Textiles at Wickliffe. - Drooker, Penelope Ballard (University of Alabama Press, 2012)
Because textiles rarely are preserved in the archaeological record outside of deserts and permafrost areas, in many regions of the world very little is known about their characteristics, functions, production technology, or socioeconomic importance. While this fact is also true of organic fabrics produced during the Mississippian period in southeastern North Anerica, a wide variety of Mississippian textiles has been preserved in the form of impressions on large pottery vessels. From attribute analysis of 1,574 fabrics impressed on Wickliffe pottery sherds and comparison of the impressions wi.